A review of criteria for outdoor classroom in selected tertiary educational institutions in Kuala Lumpur - Mohd. Yaman, Maheran; Abdullah, Fadzidah; Rozali, Nur Fadhillah; Salim, Farha (IOP Publishing, 2018)
A proper design outdoor environment in higher institutions contributes to the students’ learning performances and produce better learning outcomes. Campus surrounding has the potential to provide an informal outdoor learning environment, especially when it has the existing physical element, like open spaces and natural features, that may support the learning process. However, scholarly discourses on environmental aspects in tertiary education have minimal environmental inputs to fulfill students’ needs for outdoor exposure. Universities have always emphasized on traditional instructional methods in classroom settings, without concerning the importance of outdoor classroom towards students’ learning needs. Moreover, the inconvenience and discomfort outdoor surrounding in campus environment offers a minimal opportunity for students to study outside the classroom, and students eventually do not favor to utilize the spaces because no learning facility is provided. Hence, the objective of this study is to identify the appropriate criteria of outdoor areas that could be converted to be outdoor classrooms in tertiary institutions. This paper presents a review of scholars’ work in regards to the characteristics of the outdoor classrooms that could be designed as part of contemporary effective learning space, for the development of students’ learning performances. The information gathered from this study will become useful knowledge in promoting effective outdoor classroom and create successful outdoor learning space in landscape campus design. It I hoped that the finding of this study could provide guidelines on how outdoor classrooms should be designed to improve students’ academic achievement.